Sintesis, Molecular Docking dan Aktivitas Sitotoksik Senyawa Analog Kalkon Berbasis Alfa Tetralone terhadap Sel Kanker Payudara MCF-7: Synthesis, Molecular Docking, and Cytotoxic Activity of Alpha Tetralone Based Chalcone Analogue Compounds against MCF-7 Breast Cancer Cells - Rahmadani, Agung; Tasya, Indriana; Lestari, Wahyu Yunita; Kadir, Nurdianah Abdul; Saputri, Mitha; Erika, Farah; Usman, Usman; Sukemi, Sukemi; Arifian, Hanggara; Salam, Supriatno; Herman, Herman; Rijai, Laode (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2024)
The chalcone compound is a precursor of flavonoid and pyrazoline compounds. Chalcone has two aromatic rings (A and B) and one ?,?-unsaturated carbon atom. Chalcone compounds can be synthesized via the Claisen Schmidt condensation reaction. Chalcone synthesis uses the basic ingredients of alpha tetralone and benzaldehyde analogues. In this research, chalcone synthesis took place for 48 hours at room temperature. Synthetic materials using ethanol solvent and sodium hydroxide catalyst, as well as basic ingredients alpha tetralone, 3,4-dimethoxybenzaldehyde and 4-methoxybenzaldehyde. Characterization of synthesized compounds using spectroscopic methods, including 1H-NMR, 13C-NMR, Fourier Transform Infrared (FTIR) and mass spectroscopy. Characterization results using spectroscopic methods showed that the two chalcone analogue compounds were successfully synthesized with yields above 70%. Both chalcone compounds showed low activity against MCF-7 cancer cells. Molecular docking simulations showed that both chalcone analogues produced energy levels and intramolecular interactions that were no better than 4-hydroxytamoxifen. Keywords: chalcone analogues, alpha tetralone, cytotoxic Abstrak Senyawa kalkon merupakan salah satu prekursor dari senyawa flavonoid dan pirazolina. Kalkon mengandung dua cincin aromatis (A dan B) dan satu atom karbon ?,?-tak jenuh. Senyawa kalkon dapat disintesis melalui reaksi kondensasi Claisen Schmidt. Kalkon disintesis menggunakan bahan dasar alfa tetralone dan analog benzaldehida. Dalam penelitian ini senyawa kalkon disintesis selama 48 jam pada suhu ruang menggunakan pelarut etanol dan katalis natrium hidroksida serta bahan dasar alfa tetralone, 3,4-dimetoksibenzaldehida dan 4-metoksibenzaldehida. Senyawa hasil sintesis dikarakterisasi menggunakan metode spektroskopi meliputi 1H-NMR, 13C-NMR, Fourier Transform Infrared (FTIR) dan spektroskopi massa. Karakterisasi menggunakan metode spektroskopi menunjukkan kedua senyawa analog kalkon berhasil disintesis dengan rendemen diatas 70%. Hasil pengujian sitotoksik menunjukkan bahwa kedua senyawa analog kalkon tidak aktif terhadap sel kanker payudara MCF-7. Simulasi penambatan molekuler menunjukkan bahwa kedua analog kalkon menghasilkan tingkat energi dan interaksi intramolekuler yang tidak lebih baik dibandingkan dengan 4-hidroksitamoksifen. Kata Kunci: analog kalkon, alfa tetralone, sitotoksik